Pricing in the sharing economy: a hedonic pricing model applied to Airbnb listings. Issue 1 (2nd January 2018) - Gibbs, Chris; Guttentag, Daniel; Gretzel, Ulrike; Morton, Jym; Goodwill, Alasdair
ABSTRACT: This paper examines the impact of a variety of variables on the rates published for Airbnb listings in five large metropolitan areas in Canada. The researchers applied a hedonic pricing model to 15, 716 Airbnb listings. As expected, the results show that physical characteristics, location, and host characteristics significantly impact price. Interestingly, more reviews are associated with a drop in price. This information is useful to hosts who are forming a pricing strategy for their listings as well as for Airbnb, who needs to support them. The paper raises important questions about pricing in the sharing economy and suggests avenues for future research in this area.